Strategy for shapeing the character of students based on PAI in school - Abbas, Aries; Suriani, Suriani; Muchlis, Madian (Linguistics and Culture Review, 2021)
The formation of the character of students as the basic foundation, namely Islamic Religious Educators. The purpose of this study is to analyze, namely: (1). Planning for student learning arrangements (2). Implementation of learning on students (3). Evaluation of student learning (4). The inhibiting factor of the learning that has been carried out (5). Supporting factors of each retaliation. Conclusion: (a). Planning for the preparation of the character formation of students in improving noble character in SMA 22 has been going well and systematically (a). The implementation of student character learning is in accordance with noble character. (c). The evaluation of the implementation of character learning that has been carried out at SMA 22 has been in accordance with the instruments prepared by the teacher. (d). The obstacle factor in learning is the lack of socialization of the principal in providing enlightenment related to the preparation of the lesson plan (e). Supporting factors from the principal involving teachers and school committees and stakeholders in the preparation of the RPP.